Platelet indices in graves disease, especially plateletcrit - Saliha Yildiz; Elif Eker (Medicine Science, 2020)
Graves disease is an autoimmune thyrotoxicosis caused by thyroid receptor antibody and occurs in 1% of the population. Autoimmune events develop against cells in various tissues, including platelets. Platelet lymphocyte interaction can regulate these events. We investigated this relationship in our study. We compared leukocyte and platelet indices in 66 Graves patients and 38 control patients from hemogram parameters prospectively. Lymphocyte count, neutrophil count, platelet lymphocyte ratio, neutrophil lymphocyte ratio was insignificant between the two groups (p: 0.51, 0.13, 0.19, 0.097, respectively). Platelet count, PDW and PCT were significantly higher in Graves patients (p: 0.02, 0.03, 0.00, respectively), and MPV was significantly lower (p: 0.007). In the ROC curve analysis, the PCT threshold value was 0.24. Platelet indices in graves patients and especially PCT were more correlated with the disease than other hemogram parameters. This finding may help to clarify the pathogenesis of the disease. [Med-Science 2020; 9(2.000): 338-42]